A Combinatorial Interplay Among the 1-Aminocyclopropane-1-Carboxylate Isoforms Regulates Ethylene Biosynthesis in Arabidopsis thaliana - Tsuchisaka, Atsunari (Genetics Society of America, 2009)
Ethylene (C(2)H(4)) is a unique plant-signaling molecule that regulates numerous developmental processes. The key enzyme in the two-step biosynthetic pathway of ethylene is 1-aminocyclopropane-1-carboxylate synthase (ACS), which catalyzes the conversion of S-adenosylmethionine (AdoMet) to ACC, the precursor of ethylene. To understand the function of this important enzyme, we analyzed the entire family of nine ACS isoforms (ACS1, ACS2, ACS4-9, and ACS11) encoded in the Arabidopsis genome. Our analysis reveals that members of this protein family share an essential function, because individual ACS genes are not essential for Arabidopsis viability, whereas elimination of the entire gene family results in embryonic lethality. Phenotypic characterization of single and multiple mutants unmasks unique but overlapping functions of the various ACS members in plant developmental events, including multiple growth characteristics, flowering time, response to gravity, disease resistance, and ethylene production. Ethylene acts as a repressor of flowering by regulating the transcription of the FLOWERING LOCUS C. Each single and high order mutant has a characteristic molecular phenotype with unique and overlapping gene expression patterns. The expression of several genes involved in light perception and signaling is altered in the high order mutants. These results, together with the in planta ACS interaction map, suggest that ethylene-mediated processes are orchestrated by a combinatorial interplay among ACS isoforms that determines the relative ratio of homo- and heterodimers (active or inactive) in a spatial and temporal manner. These subunit isoforms comprise a combinatorial code that is a central regulator of ethylene production during plant development. The lethality of the null ACS mutant contrasts with the viability of null mutations in key components of the ethylene signaling apparatus, strongly supporting the view that ACC, the precursor of ethylene, is a primary regulator of plant growth and development.